Pengembangan LKPD Berbasis Project Based Learning untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPAS Kelas V - Valensi, Bunga; Rahmi, Ulfia; Zen, Zelhendri; Anugrah, Septriyan (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop Student Worksheets (LKPD) based on Project Based Learning (PjBL) in improving learning outcomes in class V science subjects. The research method used is research and development using the 4D model. Research stages include define, design, development, and disseminate. The instruments used in this research were observation, interviews, documentation, and questionnaires. The validity test was carried out by 3 validators, namely 2 media validators and 1 material validator.  Based on the results of the needs analysis, PjBL-based LKPD teaching materials are needed to improve student learning outcomes. The practicality test was carried out on 24 class V students of SD Negeri 14 Belanti Barat with the aim of finding out the practicality and effectiveness of the product. The results obtained by 2 media experts were 4.18 in the "very feasible" category. The material validation results obtained were 4.9 in the "very suitable" category. The practicality test results obtained a score of 4.35 in the "very practical" category. The results of the effectiveness test using classical completeness showed that of the 24 students who completed there were 20 students with a percentage of 83% exceeding the requirements for classical completeness, namely ≥ 75% of students who completed their learning results. This shows that the use of LKPD can improve their learning outcomes significantly